L’escrivania municipal de València en els segles XIV i XV. Notes i documents - Rubio Vela, Agustín (Caplletra. Revista Internacional de Filologia, 2015)
The influence of the Royal Chancellery, based in Barcelona, on the creation and evolution, from the xivth c. onwards, of a model of Catalan prose has already been convincingly established. This article offers new evidence of a parallel role played by some professional scribes of Valencia’s town Council.